Compassionate Use of Letermovir in a 2-Year-Old Immunocompromised Child With Resistant Cytomegalovirus Disease. (11th June 2019) - Pérez Marín, Maria; Decosterd, Laurent Arthur; Andre, Pascal; Buclin, Thierry; Mercier, Thomas; Murray, Kristina; Rizzi, Mattia; Meylan, Pascal; Jaton-Ogay, Katia; Opota, Onya; Gengler, Carole; Perez, Marie-Hélène; et al.
Abstract: Little information on the efficacy and pharmacokinetics of letermovir among immunocompromised children is currently available. We describe here the use of letermovir in a 2-year-old immunocompromised child with ganciclovir-resistant cytomegalovirus disease who required extracorporeal membrane oxygenation. Detailed information on therapeutic-drug-monitoring measures and dosage adjustments for letermovir is provided.